DIGITAL TECHNOLOGIES IN THE SYSTEM FOR ENSURING TRANSPARENCY OF CORPORATE FINANCES - ZAKНARKINA, Liudmyla; BOIKO, Artem; NEBABA , Natalia; CHUMACHENKO, Oleksandr; SHEVCHENKO, Valeriy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the impact of the use of modern digital technologies and tools by corporate enterprises on ensuring the transparency of the financial relations of such enterprises. The purpose of the work is to study the influence of modern digital technologies and tools on increasing the level of transparency and publicity of corporate finances, improving access to information, facilitating the analysis and reporting processes, and contributing to increasing the trust of investors in the enterprise. The analysis of the latest research and publications showed insufficient disclosure of this issue and the limited views of the authors on the problems of ensuring publicity and transparency of corporate enterprises in the conditions of total digitalization of business processes, which confirmed the relevance of the research. Based on the study of the experience of using modern digital technologies by enterprises, the systematization and classification of such technologies were carried out according to the purpose and application, the type of interface and interaction, and the provision of protection and security. It was determined that cloud technologies and services, Internet of Things (IoT) technologies, the use of artificial intelligence (AI) and machine learning (ML), analytics and data processing technologies, and blockchain technologies have the greatest impact on ensuring the publicity and transparency of corporate finances, their transparency. enterprise resource planning (ERP) systems, cyber security technologies. The influence of these technologies on the formation of transparency of corporate finances was analyzed, both from the point of view of positive influence and the possibility of creating potential threats and risks related to cyber security, and loss of control over financial data, which negatively affects the transparency of the company's finances. It is concluded that information technology enables effective management of large volumes of data, providing financial managers with convenient tools for analysis and data-based decisions. Modern information technologies, especially cloud solutions, allow centralized storage and management of financial data, ensuring transparency and availability of information for management and auditing.
Keywords: digital technologies; corporate finance; transparency; cloud services; Internet of Things; artificial intelligence; and machine learning; blockchain; cyber security